2001
DOI: 10.1111/j.1749-6632.2001.tb03802.x
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Uterine Receptivity in 2001

Abstract: The understanding and control of embryo implantation represents the major challenge for assisted reproductive technologies. Along with developments in basic research and efforts to optimize embryo quality, the improvement of noninvasive and reliable methods to assess uterine receptivity constitutes an important step toward meeting such a challenge. Today, ultrasound-based approaches to evaluate endometrial echogenicity and uterine perfusion and contractility are available for practical use. Increasing evidence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(8 citation statements)
references
References 91 publications
(179 reference statements)
0
6
0
2
Order By: Relevance
“…A variety of studies have suggested that ultrasound can be used as a noninvasive and simple method to assess the endometrial receptivity [52] . Several sonographic parameters have been evaluated, including EMT, endometrial pattern, endometrial volume and endometrial and subendometrial blood ow [53][54][55][56][57] .…”
Section: Discussionmentioning
confidence: 99%
“…A variety of studies have suggested that ultrasound can be used as a noninvasive and simple method to assess the endometrial receptivity [52] . Several sonographic parameters have been evaluated, including EMT, endometrial pattern, endometrial volume and endometrial and subendometrial blood ow [53][54][55][56][57] .…”
Section: Discussionmentioning
confidence: 99%
“…Up to 85% of the embryos replaced into the uterine cavity fail to implant [39]. This, in addition to the quality of the embryos, very much depends on the overall uterine receptivity and the timing of the embryo transfer (ET) [40] [41]. Since the introduction of Assisted Reproduction there has been a significant progress in improving ovarian stimulation, oocyte retrieval, IVF and embryo transfer.…”
Section: Discussionmentioning
confidence: 99%
“…Although the importance of angiogenesis for implantation, and normal uterine and placental function is well recognized [16,42,43], the role of inadequate vascularization or blood flow in implantation failure has not been investigated in detail. Inconsistent results of impact of uterine blood flow in implantation failure measured by ultrasound technologies were obtained [16,17]. For example, using ultrasound techniques [44], reduced endometrial and subendometrial 'perfusion' has been demonstrated which suggests a reduced vascularity in women with unexplained subferitility, irrespective of E2 and progesterone levels.…”
Section: Discussionmentioning
confidence: 99%